1996
DOI: 10.1289/ehp.96104s4809
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in fetal thymic and liver hematopoietic cells as indicators of exposure to developmental immunotoxicants.

Abstract: Recent studies indicate that immune development in humans and other species may be altered after perinatal exposure to immunotoxic environmental contaminants. However, limited information is available regarding appropriate tests that may adequately detect developmental immunotoxic compounds. Experiments in which pregnant laboratory rodents were exposed to a variety of immunotoxic environmental agents indicate that fetal thymus and liver immune cells may be quantitatively and qualitatively altered by immunotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Thymic atrophy, a key event that may lead to inefficient functioning of the immune system, has been reported in bacterial and viral infections, graft versus host-disease, tumor development, and following exposure to immunosuppressive chemicals (Frawley et al, 2011;Haynes et al, 2000;Holladay & Luster, 1996;Taub & Longo, 2005). In the present study, ANE (25 mg/kg) administration reduced the number of both immature thymic cells and mature CD4 þ and CD8 þ lymphocytes.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Thymic atrophy, a key event that may lead to inefficient functioning of the immune system, has been reported in bacterial and viral infections, graft versus host-disease, tumor development, and following exposure to immunosuppressive chemicals (Frawley et al, 2011;Haynes et al, 2000;Holladay & Luster, 1996;Taub & Longo, 2005). In the present study, ANE (25 mg/kg) administration reduced the number of both immature thymic cells and mature CD4 þ and CD8 þ lymphocytes.…”
Section: Discussionsupporting
confidence: 54%
“…For example, mice exposed to halogenated and polycyclic aromatic hydrocarbons demonstrate impaired thymocyte maturation and increased susceptibility to infections (Drela, 2006;Lutz et al, 1998). There are diverse mechanisms involved in chemicalinduced thymus atrophy, such as alterations in bone marrowderived thymocyte precursors, direct toxic effects on thymocytes or thymic epithelial cells, and/or induction of adrenal glucocorticoids (Comment et al, 1992;Holladay & Luster, 1996;Lundberg, 1991). It has been demonstrated that glucocorticoids inhibit thymocyte functions and induce thymocyte apoptosis in vivo (Young et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…+ fetal thymocytes and significantly increase the relative percentage of CD4-CD8-and CD4-CD8 + fetal thymocyte subsets (Holladay and Luster, 1996).…”
Section: Immune Effects Of Tcdd In Rodentsmentioning
confidence: 93%
“…The carcinogenic potential of pyrethroids was also reported on the murine model (9). A few recent studies revealed that besides blocking neurotransmission, both pyrethroids and organophosphate pesticides can cause immunosuppression and deregulation of many signalling molecules (10)(11)(12)(13)(14)(15). Organophosphates (derivatives of phosphonic acid) and systemic azole fungicides have profound cytotoxic activities, too (16,17).…”
mentioning
confidence: 99%